Geopark Rinjani, Sport Tourism, and the Rise of Local Participation Post COVID in Lombok, Indonesia - BONANG, Dahlia; HASANAH, Shofia Mauizotun; NUGROHO, M. Setyo; SYUKRIATI, Syukriati; ZULPAWATI, Zulpawati; FITRIYAH, Any Tsalasatul (Journal of Environmental Management and Tourism, 2022)
This study aims to determine the role model of local community participation in the post-pandemic Rinjani geopark sport tourism festival. The pandemic has caused a shift in tourism to focus on Nature, Eco, Wellness, and Adventure (NEWA). For this reason, the local community of Sembalun Village, a key gateway to an arduous trek up Mount Rinjani in West Nusa Tenggara Province, initiated a sport tourism event due to the natural resource potentials. Hence, this qualitative descriptive research unveils several motivations that underlie the festival's implementation, including economic, cultural, and natural environmental factors—a role model for local community participation based on these driving factors with a Bottom-Top approach.